Exercise 2.3.1 (Lemma 2.3.2)

2.3.1. Prove Lemma 2.3.2 (Hint: modify the proofs of Lemmas 2.2.2, 2.2.3 and Proposition 2.2.4)

  • \(\bullet\) Show that \(\forall n \forall m \in \mathbb{N}.~ n \times m = m \times n\).

  • \(\Vdash\) { Proof by induction on \(n\) }

    • \(\bullet\) Base case: show that \(\forall m \in \mathbb{N}.~ 0 \times m = m \times 0\)
    • \(\Vdash\) \(\forall m \in \mathbb{N}.~ 0 \times m = m \times 0\)
    • \(\equiv\) { Definition 2.3.1: \(0 \times m := 0\) }
    • \(~~~\) \(\forall m \in \mathbb{N}.~ 0 = m \times 0\)
    • \(\equiv\) { Proof by induction on \(m\) }
      • \(\bullet\) Base case: show that \(0 = 0 \times 0\)
      • \(\Vdash\) \(0 \times 0\)
      • \(\equiv\) { Definition 2.3.1: \(0 \times m := 0\) }
      • \(~~~\) True
      • \(\square\)
      • \(\bullet\) Inductive step: show that \(0 = (m\pp) \times 0\) when
      • \(\textnormal{--}\) \(0 = m \times 0\)
      • \(\Vdash\) \((m\pp) \times 0\)
      • \(=\) { Definition 2.3.1: \((n\pp) \times m := (n \times m) + m\) }
      • \(~~~\) \((m \times 0) + 0\)
      • \(=\) { Induction Hypothesis: }
      • \(~~~\) \(~~~\) \(0 + 0\)
      • \(=\) { Definition 2.2.1: \(0+m := m\) }
      • \(~~~\) \(0\)
      • \(\square\)
    • \(\square\)
    • \(\bullet\) Inductive step: show that \(\forall m \in \mathbb{N}.~ (n\pp) \times m = m \times (n\pp)\) when
    • \(\textnormal{--}\) \(\forall m \in \mathbb{N}.~ n \times m = m \times n\)
    • \(\Vdash\) \(\forall m \in \mathbb{N}.~ (n\pp) \times m = m \times (n\pp)\)
    • \(\equiv\) { Definition 2.3.1: \((a\pp) \times b := (a \times b) + b\) }
    • \(~~~\) \(\forall m \in \mathbb{N}.~ (n \times m) + m = m \times (n\pp)\)
    • \(\equiv\) { Induction hypothesis: \(\forall m \in \mathbb{N}.~ n \times m = m \times n\) }
    • \(~~~\) \(\forall m \in \mathbb{N}.~ (m \times n) + m = m \times (n\pp)\)
    • \(\equiv\) { Proof by induction on $m$}
      • \(\bullet\) Base case: show that \((0 \times n) + 0 = 0 \times (n\pp)\)
      • \(\Vdash\) \((0 \times n) + 0 = 0 \times (n\pp)\)
      • \(\equiv\) { Definition 2.3.1: \(0 \times b := 0\) }
      • \(~~~\) 0 + 0 = 0
      • \(\equiv\) { Definition 2.2.1: \(0+b := b\) }
      • \(~~~\) True
      • \(\square\)
      • \(\bullet\) Inductive step: show that \(((m\pp) \times n) + (m\pp) = (m\pp) \times (n\pp)\) when
      • \(\textnormal{--}\) \((m \times n) + m = m \times (n\pp)\)
      • \(\Vdash\) \(((m\pp) \times n) + (m\pp)\)
      • \(=\) { Definition 2.3.1: \((a\pp) \times b := (a \times b) + b\) }
      • \(~~~\) \(((m \times n) + n) + (m\pp)\)
      • \(=\) { Addition is associative }
      • \(~~~\) \((m \times n) + (n + (m\pp))\)
      • \(=\) { Definition of Addition }
      • \(~~~\) \((m \times n) + (n + m)\pp\)
      • \(=\) { Addition is commutative }
      • \(~~~\) \((m \times n) + (m + n)\pp\)
      • \(=\) { Definition of Addition }
      • \(~~~\) \((m \times n) + (m + n\pp)\)
      • \(=\) { Addition is associative }
      • \(~~~\) \(((m \times n) + m) + n\pp\)
      • \(=\) { Induction hypothesis }
      • \(~~~\) \(m \times (n\pp) + n\pp\)
      • \(=\) { Definition 2.3.1: \((a\pp) \times b := (a \times b) + b\) }
      • \(~~~\) \((m\pp) \times (n\pp)\)
      • \(\square\)
    • \(\square\)
  • \(\square\)

Links to this page